Short Communication: West Nile fever imported from Austria to Germany. Issue 2 (7th December 2018) - Pietsch, Corinna; Trawinski, Henning; Lübbert, Christoph; Liebert, Uwe G.
Abstract: This is the first report of West Nile virus (WNV) infection imported by a traveller returning from a neighbouring country to Germany (Austria). Physicians should be aware of the expansion of WNV endemic areas in Europe.